2011
DOI: 10.1136/adc.2011.212001
|View full text |Cite
|
Sign up to set email alerts
|

Fitness to fly testing in term and ex-preterm babies without bronchopulmonary dysplasia

Abstract: Ex-preterm babies without BPD and who are at least 3 months CGA do not appear to be a particularly at-risk group for air travel, and routine preflight testing is not indicated. Feeding babies in an FiO(2) of 0.15 leads to a further fall in SpO(2), which is significant but transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Similar results to these were found in previous studies conducted on older infants, as in the studies of Bossley et al, 7 who tested term and preterm infants of 3 and 6 months CGA, and Martin et al, 15 who tested healthy term infants (13-221 weeks old) and found that only 1 of 24 healthy children desaturated.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results to these were found in previous studies conducted on older infants, as in the studies of Bossley et al, 7 who tested term and preterm infants of 3 and 6 months CGA, and Martin et al, 15 who tested healthy term infants (13-221 weeks old) and found that only 1 of 24 healthy children desaturated.…”
Section: Discussionsupporting
confidence: 79%
“…It is true that active sleep, changes of position (which can influence the obstruction of the upper airway), and feeding may have an impact on oxygen saturation. [5][6][7] Therefore, we decided to standardize conditions as much as possible and tried to avoid introducing variables. The BTS guidelines do not establish recommendations in reference to the mentioned conditions even though they can have an important impact on the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporting the nadir SpO 2 value as result of a HCT could result in an overestimation of the risk. In studies of infants and children either SpO 2 at steady state17 18 or nadir SpO 2 after continuous measurement for 20 min19 have been reported, with a few studies reporting more in detail that the subjects failed the test, if SpO 2 fell ≤85% for >2 min or ≤75% for 1 min20 or SpO 2 fell <90% for a minimum of 2 min 21. In the present study both the median SpO 2 in the last 2 min, regarded as a more stable response to the hypoxic environment, and the nadir SpO 2 are reported, demonstrating a certain difference in the interpretation of a HCT depending on which value is chosen as the result of the test.…”
Section: Discussionmentioning
confidence: 99%
“…For young infants, studies show that HAST by means of a face mask does not adequately rule out in-flight desaturation [ 13 ]. Testing in a body plethysmograph is probably much more reliable, but to date, no study has included follow-up with measurements while flying [ 14 ]. If necessary, on-board oxygen can be safely administered by a portable oxygen concentrator (POC).…”
Section: Medical Assessment Of Fitness To Fly In Childrenmentioning
confidence: 99%